From Rural to Urban: Understanding Taobao Villages to Redress Planetary Urbanisation - Ruyang Sun; Manfredo Manfredini (International Journal of Urban Design and Development, 2025)
This study examines Taobao Villages as an innovative model of urbanisation under China’s planetary urbanisation framework. These rural communities, driven by the rise of e-commerce and digital infrastructure, have successfully integrated into the broader urban ecosystem by reconfiguring their historical socio-spatial legacies. Through Lefebvre’s spatial triad framework, the research identifies three key historical legacies that underpin this transformation: (1) Collective Production Practices: Rooted in socialist collectivisation, these legacies include organisational capacity, efficient labour division, and shared property management. These factors facilitated the rapid adaptation of platform-based production systems. (2) Trans local Social Relations: Kinship and geographical ties fostered a strong capacity for collective action and socio-spatial embeddedness, enhancing community networks in a digitally connected era. (3) Adaptive Livelihood Customs: The region’s history of resilience to Yellow River perturbations instilled flexibility in labour forms and migration capacities, enabling communities to thrive in volatile digital economies. The findings reveal that Taobao Villages challenge traditional urbanisation models by leveraging their unique historical contexts to develop diversified modes of production and connection. This research enriches planetary urbanisation theory by demonstrating how rural settlements, often overlooked, play a critical role in shaping urban ecosystems. By combining historical analysis with modern technological frameworks, it proposes a nuanced approach to understanding differential urbanisation patterns in the context of globalised production systems.
Keywords: Planetary urbanisation; Taobao Villages; digital e-commerce; rural-urban integration; translocalism